Relationship between evaporation and other , meteorological factors (MAUSAM, 1972)
Using correlation techniques, an assessment is made of the influence exerted by basic meteorological factors in controlling .the evoporative power of air. Linear regression equations are developed for twenty five stations linking pan evaporation with saturation vapour pressure deficit, maximum temperature and mean daily wind speed. Evaporation computed with formulation thus developed compares favourably with actual data.